Drug Review on Medhya Effect of Yastimadhu w.s.r Nootropic Effect (AYUSHDHARA, 2025)
Herbal medicines are increasingly sought after across both developed and developing nations for primary healthcare needs, largely due to their proven efficacy, favourable safety profiles, and minimal adverse effects. In the traditional system of Indian medicine, Yashtimadhu (Glycyrrhiza glabra) is one of the important neuro-nutrient herbs (Medhya Rasayana) mentioned in Ayurveda texts. Glycyrrhiza glabra is a perennial herb indigenous to the Mediterranean region and parts of Asia. The plant’s root is the primary component used in herbal formulations, valued for its broad spectrum of pharmacological properties. Acharya Charak had mentioned about four Medhya Rasayanas specifically, in which Yastimadhu is one of them, which are traditionally recommended for enhancing cognitive functions, improving concentration, boosting intelligence, and supporting overall mental performance. Glycyrrhiza glabra contains a diverse array of bioactive chemical constituents that contribute to enhanced brain function and cognitive performance. Among these are L-Phenylalanine and L-Tyrosine (including its more bioavailable form, N-Acetyl-L-Tyrosine), both of which are associated with cognitive enhancement. Along with its nootropic effects, it is also acclaimed for its hepatoprotective effects, gastroprotective effects, expectorant properties, neuroprotective actions, antiviral efficacy, anticancer potential, and anti-inflammatory activity.